2019
DOI: 10.1186/s12864-019-5882-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, phylogeny, evolutionary expansion and expression analyses of bZIP transcription factor family in tartary buckwheat

Abstract: Background In reported plants, the bZIP family is one of the largest transcription factor families. bZIP genes play roles in the light signal, seed maturation, flower development, cell elongation, seed accumulation protein, abiotic and biological stress and other biological processes. While, no detailed identification and genome-wide analysis of bZIP family genes in Fagopyum talaricum (tarta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 99 publications
4
27
0
Order By: Relevance
“…The contribution of gene duplication events to the amplification of gene families was significantly different among different species. In addition, by comparing the quantity of the tandem repeats, i.e., 4 pairs of olive, 1 pair of soybean [31], 2 pairs of tartary buckwheat [54], 0 pairs of grape, we concluded that the contribution of tandem repeats during the evolution of OebZIP genes was limited, which is consistent with reports on grape, soybean, and tartary buckwheat. Therefore, segment gene duplication plays an important role in bZIP gene family expansion in olive.…”
Section: Evolutionary Analysis Of the Oebzip Gene Familysupporting
confidence: 89%
See 3 more Smart Citations
“…The contribution of gene duplication events to the amplification of gene families was significantly different among different species. In addition, by comparing the quantity of the tandem repeats, i.e., 4 pairs of olive, 1 pair of soybean [31], 2 pairs of tartary buckwheat [54], 0 pairs of grape, we concluded that the contribution of tandem repeats during the evolution of OebZIP genes was limited, which is consistent with reports on grape, soybean, and tartary buckwheat. Therefore, segment gene duplication plays an important role in bZIP gene family expansion in olive.…”
Section: Evolutionary Analysis Of the Oebzip Gene Familysupporting
confidence: 89%
“…With respect to numbers and aa length, compared to other plants, Arabidopsis (78, 321 aa) [38], rice (89, 311 aa) [29], sesame (63, 339 aa) [30], soybean (160, 343 aa) [31], grape (47, 336 aa) [32], and apple (114, 411 aa) [35], the number of bZIP family members in olive is larger and similar to apple, while the coding sequence length of the genes is clearly different. Several studies [53,54] have found that there is no positive correlation between the numbers of bZIP genes and the genome size. The differences in the number of bZIP members in plants might be due to whole-genome duplication (WGD) events [37].…”
Section: Evolutionary Analysis Of the Oebzip Gene Familymentioning
confidence: 99%
See 2 more Smart Citations
“…The cDNA was produced by 1 mg RNA sample with a Prime Script RT Reagent Kit with gDNA Eraser (TaKaRa) with SYBR Premix Ex Taq II (TaKaRa). Expression pattern of FtHsf genes identified in different tissues (stems, roots, leave, fruits and flowers) and fruits at three different stages (13, 19 and 25 DAP) from five strains of Tartary buckwheat were analyzed with qRT-PCR, and each Tartary buckwheat was analyzed three times [35]. The qRT-PCR primers of FtHsf genes listed in Additional file 4: Table S4 were obtained by Primer3 software (Additional file 4).…”
Section: Methodsmentioning
confidence: 99%